'I cried power': The (Im)Possibility of Female 'Freedom' in Le Jour où Nina Simone a cessé de chanter (Darina Al-Joundi). Issue 1 (March 2014) - Vassallo, Helen
<x xml:space="preserve">Abstract</x> Le Jour où Nina Simone a cessé de chanter narrates Darina Al-Joundi's experiences of the Lebanese civil war, and a restriction that is personal, social, gendered and religious. It represents a resistance through performance, via appropriation of a combative persona and of secular lyrics by Nina Simone which Al-Joundi uses to 'cry power' by collapsing boundaries between self and other, East and West, thought and experience. This article analyses the tension between imposed restrictions and a desired 'freedom', setting established theories of exile (Said) in dialogue with more specific discussions of Lebanon and its social restriction of women. This interrogates the ways in which a putative 'freedom' is constructed or diagnosed as 'madness', concluding that the only possibility for negotiating any measure of real 'freedom' is in crossing borders and developing a new model of female 'freedom' contingent on the fragile and ever-shifting boundaries between representations of East and West.